Assessing consumer value through willingness-to-pay for varying attributes within a Kansas agritourism wedding event space for the application of a business modeling decision tool - Cullop, Jared (Kansas State University, 2019)
Given decreased farm profitability over last several years, this research focused on alternatives that farm operators can sustain or increase farm incomes while potentially creating economic relief for a returning generation. Decreased profits have caused younger generation farmers to consider moving away from the farm and rural communities. Economic conditions of these communities have deteriorated due to shift in population from rural toward more urban areas. With fewer members of society directly associated with agriculture, a disconnect has been created generating distrust in modern farming practices. Agritourism in general and specifically event space used as a wedding venue, has been a rapidly developing opportunity that may meet the above-stated objectives. Just like any new business undertaking, an understanding of how consumers make decisions are pertinent for the analyst to model the business as well as planning how to efficiently market the business. Using conjoint analysis, a choice-based conjoint (CBC) survey was developed and deployed regarding varying combinations of attributes related to wedding venues at specific price points. Data regarding consumer choices were evaluated using mixed logit regressions. Using the regression output, willingness to pay (WTP) values were calculated to represent utility value. Once the consumer side was analyzed, the producer side was considered for operators interested in implementing this research on their farms. An operations research business modeling decision tool was parameterized with the WTP values to represent values that can be added to the prices charged for the space if that respective option were added to the event space. The producer’s decision-making tool was built within a spreadsheet (Microsoft Excel) such that potential users will be able to find the profit maximizing bundles of the varying sizes in venue space, capacity, amenities provided, etc. A profit value is calculated based on the user’s set of parameters taking into consideration the following values: price per event, number of events per year, construction costs, and the monthly/yearly costs associated with operating the venue. This information is crucial to understand for any farmers interested in agritourism, specifically wedding venue space. If the profit value is sufficiently high, wedding venues could be used as an additional enterprise to keep younger generations on the farm and assist rebuilding rural communities.
Keywords: Economics; Agritourism; Kansas; Wedding venues; Willingness-to-pay; Operations research